ChemInform Abstract: Expedient Strategy for the Synthesis of 5‐Acylethynylpyrrole‐2‐carbaldehydes. Issue 41 (October 2015) - Tomilin, Denis N.; Sobenina, Lyubov N.; Markova, Marina V.; Gotsko, Maxim D.; Ushakov, Igor A.; Smirnov, Vladimir I.; Vaschenko, Alexander V.; Mikhaleva, Albina I.; Trofimov, Boris A.
Abstract using acetal protection of the aldehyde functionality